A Novel Design Eco-friendly Microwave-assisted Cu–N@CQDs Sensor for the Quantification of Eravacycline via Spectrofluorimetric Method; Application to Greenness Assessments, Dosage Form and Biological Samples - Salman, Baher I. (Journal of fluorescence, 2023)
Community-acquired pneumonia is one of the most common infectious diseases and a substantial cause of mortality and morbidity worldwide. Therefore eravacycline (ERV) was approved by the FDA in 2018 for the treatment of acute bacterial skin infections, GIT infections, and community-acquired bacterial pneumonia caused by susceptible bacteria. Hence, a green highly sensitive, cost-effective, fast, and selective fluorimetric approach was developed for the estimation of ERV in milk, dosage form, content uniformity, and human plasma. The selective method is based on the utilization of plum juice and copper sulphate for the synthesis of green copper and nitrogen carbon dots (Cu–N@CDs) with high quantum yield. The quantum dots' fluorescence was enhanced after the addition of ERV. The calibration range was found to be in the range 1.0 – 80.0 ng mL −1 with LOQ equal to 0.14 ng mL −1 and LOD was found to be 0.05 ng mL −1 . The creative method is simple to deploy in clinical labs and therapeutic drug health monitoring system. The current approach has been bioanalytically validated using US-FDA and validated ICH criteria. High-resolution transmission electron microscopy (HR-TEM), X-ray photon spectroscopy (XPS), Zeta potential measurements, fluorescence, UV–VIS, and FTIR spectroscopy have all been used to fully characterize the Cu–N@CQDs. The Cu–N@CQDs were effectively applied in human plasma and milk samples with a high percentage of recovery ranging from 97.00 to 98.80%.